HUBUNGAN GAYA KEPEMIMPINAN KEPALA RUANG RAWAT YANG DIPERSEPSIKAN OLEH PERAWAT PELAKSANA TERHADAP KEPUASAN KERJA PERAWAT PELAKSANA DI RUMAH SAKIT - Yohan Wenas Gunawan; Setyowati; Andreasta Meliala (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: Nurses are the biggest health personnel in the hospital. Despite their important role in providing services to patients, their job satisfaction is still low. Leadership is one of the factors affecting the nurses’ job satisfaction. Objective: The research was conducted to measure the relationship between head nurse leadership style and nurses’ job satisfaction in hospital wards. Methods: This study was an analytic research using crosssectional design. This research was conducted in the District Hospital on May 2015. Subjects were 156 nurses who work in the general and special wards. Questionnaire was divided into 3 sections, demography variable, job satisfaction using Mueller- McCloskey Satisfaction Scale and leadership style using “Multiple Leadership Questionnaire 5x”. Results: Marital status, educational level, and type of ward have a significant relationship with job satisfaction with p value of 0,033, 0,010, and 0,007 respectively. Transformational leadership style also has a significant relationship to job satisfaction, providing four times greater job satisfaction compared to passive avoidant style (p = 0,01). Conclusion: There is a relationship between head nurse’ leadership style and nurse job satisfaction. Hospital management has to give serious attention on nursing leadership to enhance attending nurses’ job satisfaction.